PERAN KEPEMIMPINAN DIGITAL DALAM MENDORONG PERILAKU INOVATIF DI ORGANISASI PENDIDIKAN: TINJAUAN LITERATUR - Malahayati, Rahmi; Rori Dolayance; Nurhizrah Gistituati; Rusdinal; Nellitawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of digital leadership in fostering innovative behavior within educational organizations. The approach used is qualitative with a literature review method, which involves examining various scientific sources such as journals, books, and relevant policy documents. The findings indicate that digital leadership plays a crucial role in developing innovative behavior through the integration of technology with organizational culture, strengthening collaboration, and enhancing human resource competencies and digital literacy. Digital leadership does not operate directly but works through organizational mechanisms such as innovation culture, transformational leadership style, and a supportive work environment. However, its implementation still faces several challenges, including resistance to change, limited digital competencies, non-adaptive organizational culture, and inadequate infrastructure. Therefore, a holistic leadership approach is needed by balancing technological and human aspects to create sustainable innovation within educational organizations.